Microdevices: tools for medical applications - Chamorro Fuertes, John Euler; Vivas Albán, Oscar Andrés (Ingeniería Solidaria, 2022)
Abstract: This article reviews the literature on the latest advances in microdevices for medical applications. The objective is to show an overview of the latest devices and their applications, as well as future development vectors in the area. A search of about 170 articles was performed, most of them published between the years 2015 and 2021, of which 53 were chosen as they were the most topical and impactful in the research fields referred to drug delivery, minimally invasive surgery, and cranial and vascular intromissions. It is concluded that, although microdevices are at an advanced stage of research, they still have many challenges to be solved, which has not allowed clinical trials to be completed in many cases. One of the great challenges ahead is to increase the precision in locomotion and to make the devices capable of performing more complex tasks with the help of smaller-scale electronic devices.